2013
DOI: 10.1002/pmic.201200350
|View full text |Cite
|
Sign up to set email alerts
|

Head and flagella subcompartmental proteomic analysis of human spermatozoa

Abstract: Subcellular proteomics not only deepens our knowledge of what proteins are present within cells, but also opens our understanding as to where those proteins reside. Given the highly differentiated, cross-linked state of spermatozoa, such studies have proven difficult to perform. In this study we have fractionated spermatozoa into two components, consisting of either the head or flagellar region. Following SDS-PAGE, 1 mm slices were digested and used for LC-MS/MS analysis. In total, 1429 proteins were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 106 publications
(143 reference statements)
7
88
1
Order By: Relevance
“…As mentioned, immunofluorescence localization of G␣ s subunit suggests that the tmAC signaling pathway is present in the sperm plasma membrane surrounding the anterior acrosome. Our results also indicate that the PKA catalytic subunit is only present in the sperm flagellum, in agreement with a recent proteomic analysis by Aitken and co-workers (72). Consistent with this differential localization, FK did not activate PKA-dependent phosphorylation in mouse sperm.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 81%
“…As mentioned, immunofluorescence localization of G␣ s subunit suggests that the tmAC signaling pathway is present in the sperm plasma membrane surrounding the anterior acrosome. Our results also indicate that the PKA catalytic subunit is only present in the sperm flagellum, in agreement with a recent proteomic analysis by Aitken and co-workers (72). Consistent with this differential localization, FK did not activate PKA-dependent phosphorylation in mouse sperm.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 81%
“…In their recent proteomic studies of sperm, Baker et al (2013) and Amaral et al(2013) identified the proteins belonging to normal sperm head and tail domains [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…SPANX B has been detected in both head and tail domains of sperm [19]. The function and exact location of this protein in flagella has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the metabolites and proteins as main determinants of the expression of the genomes and transcriptomes as also influenced by environmental cues, represents a first step to understand the normal composition and physiology of cells and tissues and their dysfunction associated with pathological states (Jodar et al, 2012;Wishart et al, 2013;Castillo et al, 2014a,b). In the case of the human spermatozoon, over 6000 proteins have been identified using mass spectrometry (MS), representing about 80% of the estimated proteome of this cell (Oliva et al, , 2009Amaral et al, 2013Amaral et al, , 2014aBaker et al, 2013;Azpiazu et al, 2014). However, and in *Correction added on 26 May 2015, after first online publication: article title corrected.…”
Section: Introductionmentioning
confidence: 99%